2011
DOI: 10.1007/s10995-011-0817-6
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Postpartum Depression Among Low-Income Mothers Using an Interactive Voice Response System

Abstract: This study tested the feasibility of using an interactive voice response (IVR) phone system to screen for postpartum depression among low-income, English- and Spanish-speaking mothers. Newly delivered mothers were interviewed in the hospital. Consenting subjects completed a background questionnaire and were asked to call an automated phone system 7 days postpartum to complete an IVR version of the Edinburgh Postnatal Depression Screen (EPDS). During the phone screen, subjects were branched to different closing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 34 publications
0
41
0
2
Order By: Relevance
“…Several studies have supported the magnitude of the effects of PPD on women, especially among minority, low-income populations, and the potential for long-lasting effects on the infant (Kim et al, 2012). The consensus among researchers is that an increased level of social support is associated with less PPD (Brown et al, 2012;Chien et al, 2012;R.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have supported the magnitude of the effects of PPD on women, especially among minority, low-income populations, and the potential for long-lasting effects on the infant (Kim et al, 2012). The consensus among researchers is that an increased level of social support is associated with less PPD (Brown et al, 2012;Chien et al, 2012;R.…”
Section: Discussionmentioning
confidence: 99%
“…8). Support is paramount, and early recognition and treatment of PPD among disadvantaged populations in particular is an urgent health issue (Kim et al, 2012). Many studies have found that increased levels of support were associated with lower PPD scores (Brown, Harris, Woods, Burman, & Cox, 2012;Chien, Tai, & Yeh, 2012; R. C. Edwards et al, 2012;Fowles et al, 2012;Quelopana, Champion, & ReyesRubilar, 2011).…”
Section: Objectivesmentioning
confidence: 99%
“…A striking prevalence of postpartum depression of 33% to almost 40% was observed among low-income mothers between three months and nine months after delivery (Gress-Smith et al, 2012;Ortiz Collado et al, 2014). However, the prevalence is low at 17.0% at seven days postpartum (Kim et al, 2012). Disaster is usually a cause of psychopathology.…”
Section: Magnitude Of Postpartum Depressionmentioning
confidence: 99%
“…Therefore, focus has been on developing systems that provide MHWs with automated diagnostics and guidance in routine actions of care [13,14,27]. Mobile apps that can aid MHWs in remotely obtaining results of ultrasound scans have been evaluated [2,17].…”
Section: Screening Devicesmentioning
confidence: 99%